Harnessing the power of AI language models for taxonomy and systematics: a follow-up to “Can ChatGPT be leveraged for taxonomic investigations? Potential and limitations of a new technology” by Davinack (2023) - Santos, Charles Morphy D.; Gois, João Paulo (Zootaxa, 2023)
N/A